Marketization in Crisis: The Political Economy of COVID-19 and the Unmaking of Public Transport in Stockholm. (March 2023) - Paulsson, Alexander; Koglin, Till
While measures to prevent the spread of COVID-19 disturbed both global and local markets, some commentators also argued that the pandemic could be seen as the beginning of the end of neoliberalism. Although neoliberal reforms have come under pressure, little is known about the implications of COVID-19 in or across specific sectors. Scaling down the rich theoretical–historical debates about neoliberalism to the regional level, we study the impact of COVID-19 on the marketized public transport system in Stockholm, Sweden. During COVID-19, ridership dropped as did ticket revenues, which put the market under operational and financial distress. Drawing on a discussion of the norms and techniques of marketization, we probe how the contracted bus operators responded to the pandemic, how they tried to save the market from collapsing, and whether the measures taken suggest an organized move away from neoliberal policies. Adding to recent debates of COVID-19 and neoliberalism's longevity, we conclude that although the norms underpinning marketization remained unquestioned, the techniques were partly re-evaluated in the midst of the global crisis as a way to protect the established neoliberal policies from falling apart.